Photocarcinogenesis & Photoprotection (Springer Singapore, 2018)
This book highlights the problem of UV-R-induced photocarcinogenesis and its molecular mechanism. It covers different photosensitive xenobiotics (drugs, cosmetics, and environmental pollutants) and their photosensitization mechanisms under ambient UV-R exposure. It also summarizes the role of nanotechnology in skin cancer remedies. It provides a brief overview of the various novel nanocarriers for cosmeceuticals like nanoemulsions, liposomes, solid lipid nanoparticles (SLNs), dendrimers, inorganic nanoparticles, nanocrystals, etc., nanotechnology-based cosmeceutical products which are available in the market. It highlights the possible health hazards caused by nanoparticles on exposure of nano-based cosmetics and describes the recent regulatory rules applied to avoid the nanotoxicity. .